(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article analyzes the contribution of dialogue to character voice development in creative writing. It deals with the aspects of writing one’s effective speech including avoiding stereotypes and tone deaf voices. Stressing the importance of individualism, subtext, and cultural contextualization, the article offers practical tools to authors who wish their characters to be interesting and believable